Influences of environmental and leaf functional traits variations on photosynthetic characteristics of Cotoneaster multiflorus in Xinglong Mountain - Han, Ling; Ma, Xiaodong; Zhao, Chengzhang; Liu, Dingyue (Frontiers in Plant Science, 2025)
Background and aimsSlope aspect affects the redistribution of solar radiation and precipitation, altering habitat conditions such as temperature, water availability, and soil nutrient composition. However, the impact of slope-induced environmental changes on the synergistic relationship between plant photosynthetic characteristics and leaf functional traits remains underexplored.MethodsFour plots of Cotoneaster multiflorus (C. multiflorus) were established on the southern, eastern, western, and northern slopes within the Xinglong Mountain National Nature Reserve. This study investigated variations in leaf functional traits, photosynthetic-fluorescence characteristics, and environmental responses in C. multiflorus across different slope aspects by mathematical statistics.ResultsOur study revealed that the southern slope demonstrated maxima in transpiration rate (Tr), coefficient of non-photochemical burst (NPQ), maximum photosynthetic efficiency of photosystem II (Fv/Fm), vein area (LVA), leaf thickness (LT), and stomatal density (SD). The eastern slope exhibited peak values in net photosynthetic rate (Pn), stomatal conductance (Gs), water use efficiency (WUE), and electron transfer rate of photosystem II (ETR). In contrast, the northern slope showed the highest intercellular CO₂ concentration (Ci), coefficient of photochemical burst (qP), actual photosynthetic efficiency of photosystem II (Y(II)), vein density (VD), and leaf area (LA). Photosynthetic-fluorescence characteristics in C. multiflorus were significantly correlated with leaf traits, vein traits, and stomatal density, with VD and SD exerting the most pronounced influences. Photosynthetic physiology on southern and western slopes was differentially modulated by temperature and moisture factors, particularly vapor pressure deficit (VPD) and photosynthetically active radiation (PAR), while the eastern slope was primarily governed by moisture and nutrient availability. Northern slope plants experienced co-regulation by temperature, soil nutrients, and moisture, with soil organic carbon (SOC) and total phosphorus (TP) exhibiting dominant effects.ConclusionsThis research underscores slope-specific adaptive mechanisms and key drivers in C. multiflorus, informing scientific cultivation practices for shrub communities in arid ecosystems.